SIMULATED ANNEALING ALGORITHM FOR FEATURE SELECTION - Rosario, Francisca; Thangadurai, Dr. K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
In the process of physical annealing, a solid is heated until all particles randomly arrange themselves forming the liquid state. A slow cooling process is then used to crystallize the liquid. This process is known as simulated annealing. Simulated annealing is stochastic computational technique that searches for global optimum solutions in optimization problems. The main goal here is to give the algorithm more time in the search space exploration by accepting moves, which may degrade the solution quality, with some probability depending on a parameter called temperature. In this discussion the simulated annealing algorithm is implemented in pest and weather data set for feature selection and it reduces the dimension of the attributes through specified iterations.